The pursuit of further miniaturization of screen printed micro paper-based analytical devices utilizing controlled penetration towards optimized channel patterning - Hsiu-Yang Tseng (Nature Portfolio, 2021)
Abstract One of the main objectives of microfluidic paper-based analytical devices is to present solutions particularly, for applications in low-resource settings. Therefore, screen-printing appears to be an attractive fabrication technique in the field, due to its overall simplicity, affordability, and high-scalability potential. Conversely, the minimum feature size attained using screen-printing is still rather low, especially compared to other fabrication methods, mainly attributed to the over-penetration of hydrophobic agents, underneath defined patterns on masks, into the fiber matrix of paper substrates. In this work, we propose the use of the over-penetration to our advantage, whereby an appropriate combination of hydrophobic agent temperature and substrate thickness, allows for the proper control of channel patterning, rendering considerably higher resolutions than prior arts. The implementation of Xuan paper and nail oil as novel substrate and hydrophobic agent, respectively, is proposed in this work. Under optimum conditions of temperature and substrate thickness, the resolution of the screen-printing method was pushed up to 97.83 ± 16.34 μm of channel width with acceptable repeatability. It was also found that a trade-off exists between achieving considerably high channel resolutions and maintaining high levels of repeatability of the process. Lastly, miniaturized microfluidic channels were successfully patterned on pH strips for colorimetric pH measurement, demonstrating its advantage on negligible sample-volume consumption in nano-liter range during chemical measurement and minimal interference on manipulation of precious samples, which for the first time, is realized on screen-printed microfluidic paper-based analytical devices.